2015
DOI: 10.1038/srep11900
|View full text |Cite
|
Sign up to set email alerts
|

TOX and CDKN2A/B Gene Polymorphisms Are Associated with Type 2 Diabetes in Han Chinese

Abstract: To study associations between type 2 diabetes (T2DM) candidate genes and microvascular complications of diabetes (MVCDs), we performed case-control association studies for both T2DM and MVCDs in Han Chinese subjects. We recruited 1,939 unrelated Han Chinese T2DM patients and 918 individuals with normal blood glucose levels as nondiabetic controls. Among T2DM patients, 1116 have MVCDs, 266 have a history of T2DM of >10 years but never developed MVCDs. Eighty-two single-nucleotide polymorphisms (SNPs) in 54 cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Higher risk of high levels of CDKN2A was found in T2DM patients with respect to controls. The previous studies also reported a significant association of CDKN2A locus with T2DM [38,39]. Further, we observed a marked increase in CDKN2A level with the increase in duration of diabetes.…”
Section: Journal Of Diabetes Researchsupporting
confidence: 87%
“…Higher risk of high levels of CDKN2A was found in T2DM patients with respect to controls. The previous studies also reported a significant association of CDKN2A locus with T2DM [38,39]. Further, we observed a marked increase in CDKN2A level with the increase in duration of diabetes.…”
Section: Journal Of Diabetes Researchsupporting
confidence: 87%
“…Several genome-wide association studies have linked the CDKN2A locus, which encodes p16 INK4a , to type 2 diabetes (Wei et al, 2015; van Hoek et al, 2008; Zeggini et al, 2007; Scott et al, 2007). However, a study examining associations between diabetes-associated polymorphisms and β-cell function and insulin sensitivity in healthy adults failed to identify a relationship between CDKN2A and metabolic impairments (Pascoe et al, 2007).…”
Section: Cellular Senescence: Aging Mechanism Activated By Nutrienmentioning
confidence: 99%
“…Variant rs7842858, has not been reported previously. SNP rs7842858 is located on TOX ( Fig 4 ), which has been reported to be associated with obesity and diabetes [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, variant rs7842858 has a positive effect on the three traits in males but negative effect in females ( Fig 5 ), which leads to the failure of detection by either conventional single trait meta-analysis or combining the three traits by S Hom . SNP rs7842858 (8:58987111) resides within TOX ( Fig 4 ), which has been reported to be associated with Type 2 Diabetes in Chinese Han population [ 20 ]. It is possible that this variant affects obesity variation and therefore indirectly contributes to Type 2 Diabetes.…”
Section: Discussionmentioning
confidence: 99%